Franz–Keldysh effect in β-Ga2O3 Schottky barrier diode under high reverse bias voltage - Takuya Maeda; Kentaro Ema; Kohei Sasaki (Applied Physics Express)
The reverse-voltage dependence of a photocurrent in a Ni/ β -Ga _2 O _3 Schottky barrier diode was investigated under sub-bandgap monochromatic illumination with wavelengths ranging from 275 to 1200 nm. Under low reverse bias conditions, a photocurrent induced by internal photoemission was observed. However, under high reverse bias conditions, the photocurrent near the absorption edge increased significantly with reverse voltage, and the increase was more pronounced for wavelengths closer to the absorption edge. Numerical calculations based on direct optical absorption induced by the Franz–Keldysh (FK) effect showed excellent agreement with the experimental data.